Renal failure in multiple myeloma "the myeloma kidney": state of the art - Goldschmidt, Hartmut; Lannert, Heinrich; Bommer, Jürgen; Ho, Anthony Dick (Saudi journal of kidney diseases and transplantation, 2001)
Renal failure is present in about 20% of patients with multiple myeloma (MM) at diagnosis. Renal function impairment is usually caused by the so-called myeloma kidney and is associated with shortened survival in patients treated with conventional therapy. Renal failure is reversible in up to 50% of patients, particularly when its degree is moderate and it is related to precipitating factors such as hypercalcemia. In our experience, approximately 10% of newly diagnosed patients with MM have renal failure severe enough to require dialysis. Despite its frequency, there are few reports dealing with MM and renal failure.
Gesehen am 21.12.2021